PENGARUH IKLAN DESAIN KEMASAN COCA COLA TERHADAP BRAND AWARENESS SISWA/SISWI SMAN 94 JAKARTA BARAT - Sari, Purnama (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2012)
Competition in the carbonated beverage industry, making manufacturers began to notice a unique packaging design to attract the attention of consumers. Problems of this research is there any effect of Product Packaging Design Advertising Coca Cola Version âFriends Cuteâ Brand Awareness Against Students / Students of SMAN 94 Jakarta Barat. The theory used Individual Differences Theory (Individual Differences Theory) and theoretical ATR (Awareness - Trial - Reinforcement), using explanatory method with a quantitative approach. Location of the research conducted at SMAN 94 Jakarta Barat. Of the 79 respondents, obtained correlation value of 0.611, which means there is a positive influence on the design of the packaging with the brand awareness of SMAN 94 Jakarta Barat.